Corporate social responsibility and shareholder wealth: New insights from information spillovers. Issue 1 (29th July 2021) - Ge, Qi; Li, Ting
Abstract: Utilizing comprehensive business news data, we examine the link between corporate social responsibility (CSR) and shareholder wealth through the information spillovers of news announcements. Specifically, we leverage competitor's news as an exogenous shock to peer firms' stock returns and explore how the resulting abnormal returns may be explained by their respective CSR performance. Our findings not only confirm an inverse relationship between CSR engagement and the size of stock market reactions but also suggest that such dampening effect may extend beyond the traditional product differentiation strategy and can be magnified with respect to the types and salience of news.